248 A 57-year-old man with deteriorating mobility and deafness. Issue 12 (14th November 2019) - Stavrou, Maria; Yeo, Jing Ming; Richard, Davenport
Abstract : A 57-year-old man re-presented to the neurology clinic in August 2014 with a 20-year history of progressive gait decline, and a 2-year history of requiring crutches and a wheelchair. Recently, he had also developed numbness below his knees. His upper limb function had remained normal. He wore bilateral hearing aids for sensorineural deafness, had a 10-year history of red–green colour blindness and suffered from bladder dysfunction for several years. His neurological symptoms had been previously investigated but without a diagnosis, and he had been lost to follow-up for several years. In 2017, with the advent of next-generation sequencing gene panel, he was screened for 20 spastic paraparesis genes. This identified a mutation in SPG7 in the form of a homozygous variant c.1529C>T/p.Ala510Val, consistent with autosomal-recessive HSP. This man's diagnosis was made by molecular genetic testing nearly 20 years after his symptoms began. This was achieved by the astonishing progress over the last decade in identifying HSP genes coupled with the introduction of high-throughput sequencing approaches. These advances provide benefits to HSP families including diagnostic certainty, avoidance of time-consuming and expensive investigations, genetic counselling and optimisation of care. A step forward would be to establish an international database of people with this condition to characterise genotype/phenotype correlations, elucidate the natural history and to facilitate clinical trials focusing on effective interventions.